2004
DOI: 10.5860/crl.65.5.427
|View full text |Cite
|
Sign up to set email alerts
|

Print versus Electronic Journal Use in Three Sci/Tech Disciplines: What’s Going On Here?

Abstract: In 2003, an evaluation of journal use statistics at Washington State University was undertaken to determine if the selection of electronic journals in the Owen Science and Engineering Library was changing student and researchers’ choice of journals. Use statistics showed that most print journals were being used more than they were prior to the advent of electronic journals. Generally, electronic journals were used heavily and the availability of electronic format greatly enhanced the total use of most titles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…after the introduction of electronic journals. Similarly, Siebenberg, Galbraith and Brady (2004) reported that most print journals were used more at the time of their study than prior to the advent of electronic journals at Washington State University. The authors contended that migration from paper to electronic journals depended on the subject area and that quality and pertinence remained the dominant factors in users' choice of journals.…”
Section: Migration From Print To Electronic Journalsmentioning
confidence: 99%
“…after the introduction of electronic journals. Similarly, Siebenberg, Galbraith and Brady (2004) reported that most print journals were used more at the time of their study than prior to the advent of electronic journals at Washington State University. The authors contended that migration from paper to electronic journals depended on the subject area and that quality and pertinence remained the dominant factors in users' choice of journals.…”
Section: Migration From Print To Electronic Journalsmentioning
confidence: 99%
“…1 The authors were trying to determine if patrons were switching from print journals to electronic merely because a title was available electronically. Unsurprisingly, this study revealed that the use of all three collections had increased with the advent of electronic access to many of the titles.…”
mentioning
confidence: 99%
“…However, Siebenberg et al (2004) concluded that most print journals at Washington State University's Owen Science and Engineering Library in 2003 were actually being used more than they were prior to the introduction of electronic journals. They argue that the availability of electronic formats has, in fact, greatly enhanced the total use of all titles.…”
Section: Use and Usage Of E-journalsmentioning
confidence: 95%